2019
DOI: 10.1108/jefas-05-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and institutional stability: who drives whom?

Abstract: Purpose The purpose of this paper is to examine the relationship between foreign direct investment (FDI) flows and institutional stability. The focus country is Canada. It is one of the few countries where the economy remained relatively stable compared to other economies during the Global Financial Crisis. It is crucial for Canada to determine the optimal level of institutional development to attract more FDI and sustain the sound financial stability in future. Design/methodology/approach This study uses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(68 reference statements)
0
15
0
1
Order By: Relevance
“…From the literature, corruption affects the level of institutional quality and of offshoring such that: Assumption 1. A lower level of corruption results in strong institutions (e.g., Mahmood, 2019; Sumanjeet, 2015); Assumption 2. the level of corruption is negatively related with the level of offshoring; that is, a lower level of corruption is related with a higher level of offshoring (e.g., Egger & Winner, 2006; Karpaty & Tingvall, 2015). Our analyses is based on these two assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature, corruption affects the level of institutional quality and of offshoring such that: Assumption 1. A lower level of corruption results in strong institutions (e.g., Mahmood, 2019; Sumanjeet, 2015); Assumption 2. the level of corruption is negatively related with the level of offshoring; that is, a lower level of corruption is related with a higher level of offshoring (e.g., Egger & Winner, 2006; Karpaty & Tingvall, 2015). Our analyses is based on these two assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, institutions are related to attributes and codes of behavior, and thus the level of corruption (Nugroho et al, 2019), and effectively affect economic performance. Institutions dictate the rules, such as norms and property rights, of each society and decide how economic individuals behave (Mahmood, 2019), imposing constraints that define how political, social, and economic aspects will interact with each other (White el al., 2019). The level of corruption is thus associated with the quality of institutions such that different institutions generate different levels of corruption.…”
Section: Introductionmentioning
confidence: 99%
“…Отличительной особенностью Гонконга в контексте привлечения ПИИ является позиционирование себя как региона с сильно развитым сектором по предоставлению юридических услуг, что привлекает многие международные компании располагать свой офис за пределами страны происхождения именно в Гонконге 15 . Большие объемы притоков ПИИ во многом объясняются реализацией инициативы «Один пояс и один путь» и тем фактом, что в Гонконге действует принцип «одна страна, две системы», учитывая, что Гонконг юридически является специальным административным районом Китая.…”
Section: а г аветисянunclassified
“…The third strand of the literature explores the effect of a composite institutional indicator, which is constructed by combining different dimensions of institutional variables. For example, Mahmood et al (2019) found a positive link between FDI and institutional stability in Canada. Aziz (2018) demonstrated that the institutional quality variables of economic freedom, ease of doing business and international country risk (ICRG) have a positive and significant impact on FDI inflows in Arab economies.…”
Section: Institutional Determinants Of Fdimentioning
confidence: 99%